Ionizing Radiation: Chemical Kinetics, Chemical Bounds, and Radiation Chemistry on Polymers - Ortega Pijeira, Martha Sahylí; Magne, Tais M.; da Silva, Natália Cristina Gomes; Ramos Ribeiro, Elisabete Regina Fernandes; Albuquerque Silva, Yuri José; Ricci-Junior, Eduardo; Rebelo Alencar, Luciana Magalhães; Santos-Oliveira, Ralph (Current Topics in Medicinal Chemistry, 2023)
Ionizing radiation has been used for decades and expanded to several applications in multivariate sectors, becoming an important tool to promote controlled chemical reactions in polymeric structures, according to their chemical properties for developing new materials. In addition, the use of radiation can also be applied in order to reduce or eliminate compounds from solutions that may be harmful or of low interest. In this review, we overviewed the chemistry behind material irradiation and the attractive use of ionizing radiation in scientific and industrial development. In this regard, the review was divided into three main sections titled (1) chemical kinetics intermediated by radiation, (2) chemical bonds intermediated by radiation, and (3) radiation chemistry on polymers. We concluded that graft polymerization, crosslinking and chain scission reactions induced by ionizing radiation are very efficient and green strategies for developing new materials with improved properties. Furthermore, water radiolysis plays a key role in the degradation of several contaminants, including pharmaceuticals and microplastics, in aqueous solutions. However, more studies must be conducted to complement the existing theory about the proposed mechanisms responsible for modifying the chemical, mechanical, thermal, optical, and so forth properties of irradiated materials.
Keywords: Radiopharmaceuticals